1854 Ky. Acts 186 - (:unkn) unknown (My University, 1853)
An Act to Prohibit the Carrying of Concealed Deadly Weapons, Ch. 1020: Be it enacted by the General Assembly of the Commonwealth of Kentucky, That if any person shall hereafter carry concealed any deadly weapons, other than an ordinary pocket knife, except as provided in the next section, he shall be fined on the first conviction not less than fifth nor more than one hundred dollars, and on any subsequent conviction not less than one hundred nor more than five hundred dollars.
Keywords: CARRY - CONCEALED